(untitled) (KYAMC Journal, 2020)
Background: Dhaka Medical College Hospital is the highest referral center for PFUI. As anstomotic urethroplasty is a challenging surgery and most of the surgeons refer these type of injuries to our center, we performed this study to evaluate the outcome of our cases. Objective: This study aims to find the outcome and complications of perineal end to end anastomotic urethroplasty in the management of posterior urethral injury resulting from pelvic fracture. Materials and Methods: We performed 147 perineal bulbo-prostatic anastomotic urethroplasty for PFUIs from January, 2013 to May, 2019. Mean age was 37 years with majority between 21 to 50 years (>85%). Nine patients had history of failed anastomotic urethroplasty. After surgical intervention patients were discharged with a supra-pubic catheter (SPC) and per urethral catheter in situ. On 22nd POD urethral catheter was removed and SPC on the next day if patient can void normally. 1st and 2nd follow up done on of 3rd and 6th month respectively following surgery. If patient voided well and Qmax>15ml/ sec; repair was defined as successful. Results: Success rate of anastomotic urethroplasty for PFUI was 93.87%. Total 9 procedures were failed including 2 urethro-cutaneous fistula and needed re-do anastomosis. Erectile dysfunction (ED) was present in 18 patients before operation and after surgery 12 more patients developed ED and total number was 30 during first follow up, which reduced to 24 during second follow-up. Two patient developed incontinence which improved in subsequent follow-up. Conclusion: Anastomotic urethroplasty remains the gold standard in the management of PFUI. Erectile dysfunction is the main issue to be concerned and need special attention. KYAMC Journal Vol. 10, No.-4, January 2020, Page 179-183